Breast cancer with pregnancy in cross cultural setting - Lasker, Shamima P (Bangladesh Journal of Bioethics, 2012)
DOI: http://dx.doi.org/10.3329/bioethics.v3i3.12561 Bangladesh Journal of Bioethics 2012; 3(3):21-26